Implementation of the Amtsilati Method in Improving the Ability to Read the Yellow Book in Islamic Schools - mahbubi, Muhammad; Shahidi, Nima; Gunawan, Ridwan (Electronic Journal of Education, Social Economics and Technology, 2024)
This article explores the implementation of the Amtsilati Method in improving the ability to read the Yellow Book in Islamic schools, particularly at M.A. Syafi'iyah Kota Anyar Probolinggo. The Yellow Book, a collection of classical Islamic texts written in Arabic, is a core element in Islamic education. However, many students face difficulties in reading and comprehending these texts due to their limited proficiency in Arabic. The Amtsilati Method, designed to facilitate Arabic language learning, is expected to address these challenges. This research adopts a qualitative approach using observation and interviews to assess the effectiveness of the Amtsilati Method in the context of Yellow Book reading instruction. The results indicate that students who participated in lessons using this method showed significant improvement in both reading and understanding Yellow Book texts. The Amtsilati Method was found to be effective in introducing the structure of Arabic systematically, helping students recognize common vocabulary and grammar found in the Yellow Book. The article concludes that the Amtsilati Method can be a valuable tool in enhancing Arabic literacy and improving students' ability to engage with classical Islamic texts in a more accessible and effective manner.